1982
DOI: 10.1080/00288330.1982.9515975
|View full text |Cite
|
Sign up to set email alerts
|

A groundwater quality survey of an unsewered, semi‐rural area

Abstract: A baseline groundwater quality survey of 120 household wells in an unsewered area at Yaldhurst, near Christchurch, was carried out between September and December, 1976. Ammonia-N levels were below the detection limit (0.02 g m-3) in all samples. Nitrate-N, conductivity, and chloride levels tended to vary according to well depth and location, being lower in the deeper wells and in wells located in an area of shallow, stony soils. Approximately 33% of the wells contained coliform bacteria, faecal coliform bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
14
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 8 publications
5
14
0
Order By: Relevance
“…Septic tank systems were considered to be the major source of fecal contamination. Subsequently, 25 wells were selected in 1977 for monitoring of fecal coliforms and NO 3 − (Sinton, 1982). These 25 wells had indicator bacteria present and high levels of electrical conductivity in the 1976 survey.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Septic tank systems were considered to be the major source of fecal contamination. Subsequently, 25 wells were selected in 1977 for monitoring of fecal coliforms and NO 3 − (Sinton, 1982). These 25 wells had indicator bacteria present and high levels of electrical conductivity in the 1976 survey.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of clustered septic tank systems on groundwater quality in New Zealand has previously been investigated in two field studies performed at a site near Christchurch, in 1977 (Sinton, 1982) and in 1986 (Close et al, 1989). Elevated NO 3 − levels and locally high fecal coliform levels in groundwater were found in both surveys.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of faecal micro-organisms in these aquifers has been demonstrated in surveys of household wells in unsewered areas (Sinton 1982;Ayrey & Noonan 1983), and in studies of ground water quality near effluent irrigation schemes and septic tank systems (Martin & Noonan 1977;Sinton 1986a). In addition, microbial tracing studies have been undertaken to determine the rates of movement of microbes in saturated gravels (Noonan & McNabb 1979;Pyle 1979;Sinton 1979Sinton ,1980aSinton ,b, 1986aSinton & Close 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, groundwater quality surveys of some unsewered communities have shown that up to 33% of household drinking water bores contain faecal bacteria (Sinton 1982;Ayrey & Noonan 1983). Although septic tank effluent was the suspected source of this contamination, animal sources could not be discounted because of uncertainties over groundwater flow directions and velocities.…”
Section: Introductionmentioning
confidence: 99%